2016
DOI: 10.1038/srep20764
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucose metabolism during in vitro maturation on cytoplasmic maturation of mouse oocytes

Abstract: Although there are many reports on the effect of glucose metabolism on oocyte nuclear maturation, there are few studies on its effect on ooplasmic maturation. By manipulating glucose metabolism pathways using a maturation medium that could support oocyte nuclear maturation but only a limited blastocyst formation without glucose, this study determined effects of glucose metabolism pathways on ooplasmic maturation. During maturation of cumulus-oocyte-complexes (COCs) with glucose, the presence of PPP inhibitor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
64
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 52 publications
7
64
1
2
Order By: Relevance
“…In a variety of mammals, glucose metabolism and pyruvate play an important role in oocyte maturation and subsequent early embryonic development [13]. In an in vitro oocyte culture system, a decrease in glucose concentration was shown to significantly inhibit meiotic divisions, subcapsular maturation, and subsequent embryonic development in bubaline and bovine oocytes[4, 5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a variety of mammals, glucose metabolism and pyruvate play an important role in oocyte maturation and subsequent early embryonic development [13]. In an in vitro oocyte culture system, a decrease in glucose concentration was shown to significantly inhibit meiotic divisions, subcapsular maturation, and subsequent embryonic development in bubaline and bovine oocytes[4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian oocytes metabolize glucose primarily through glycolysis, PPP, and the tricarboxylic acid cycle (TAC) [1, 9]. PPP and/or glycolysis appear to play a key role in the resumption of meiosis in mouse oocytes [1, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Glucose metabolism affected both oocyte maturation and following development of oocytes after fertilization and oocyte aging89. Glucose metabolism in cumulus cells prevented oocyte aging by producing pyruvate and NADPH through glycolysis and pentose phosphate pathway (PPP).…”
mentioning
confidence: 99%
“…These results suggest that proper levels of cellular ATP in MII oocytes is one of the key factors determining fertilization and early embryo development, and Gas6 is associated with ATP production and HS production. When mitochondria produce excessive ATP, they also release ROS, and ROS oxidatively damage mitochondrial DNA (mtDNA), impair mitochondrial function, and contribute to free radical formation [38,50]. In the current study, excessive mitochondrial ATP production in MII oocytes by Gas6 RNAi led to the generation of ROS.…”
Section: Discussionmentioning
confidence: 75%
“…Cytoplasmic maturation is composed of various changes within oocytes, including accumulation of mRNA and proteins, reorganization of cytoskeleton and organelles, and changes in metabolism [38]. We have previously shown that Gas6 is a mammalian maternal effect gene and is critical for cytoplasmic maturation and normal fertilization, especially Ca 2+ excitability, cortical granule exocytosis, SCD and PN formation [8].…”
Section: Discussionmentioning
confidence: 99%